Deinonychus and The Cow – Enhancing Museum Exhibitions Through the Use of Mixed Reality - Souza, Alyson Matheus de Carvalho; Arruda, Deborah Dantas; Sarmento, Carlos Eduardo; Bessa, Olavo F M; Ramos, Everardo A; Rennó-Costa, César (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2022: Anais do XXIV Simpósio de Realidade Virtual e Aumentada, 2022)
The use of technology inside museums is a topic of growing interest. Technology-driven installations not only create new experiences for the regular visitors but also may be enough to attract the interest of new ones. When those experiences happen outside of the museum walls, they can be even stronger in delivering the museum’s message to a new audience. Based on that, the Deinonychus experience and The Cow were created. These Mixed Reality (MR) experiences were first installed in a temporary facility of the Câmara Cascudo Museum during a Science, Culture, and Technology fair at the Federal University of Rio Grande do Norte’s central campus. This paper describes the development, deployment, and testing of those installations in a real environment, with considerations for those interested in creating something similar. Finally, the paper discusses the solutions used and how they could be replicated for museums around the globe.